# USE SUBSTITUTION TO SOLVE EACH SYSTEM OF EQUATIONS

Use Substitution to Solve Each System of Equations :

In this section, you will learn how to solve a system of linear equations with two unknowns using substitution.

## Solving System of Equations by Substitution - Steps

Step 1 :

In the given two equations, solve one of the equations either for x or y.

Step 2 :

Substitute the result of step 1 into other equation and solve for the second variable.

Step 3 :

Using the result of step 2 and step 1, solve for the first variable.

## Use Substitution to Solve Each System of Equations

Problem 1 :

Solve the following system of equations using substitution.

-4x + y = 6  and  -5x - y = 21

Solution :

-4x + y  =  6 -----(1)

-5x - y  =  21 -----(2)

Step 1 :

Solve (1) for y.

-4x + y  =  6

y  =  6 + 4x -----(3)

Step 2 :

Substitute (6 + 4x) for y into (2).

(2)-----> -5x - (6 + 4x)  =  21

-5x - 6 - 4x  =  21

Simplify.

-9x - 6  =  21

-9x  =  27

Divide each side (-9).

x  =  -3

Step 3 :

Substitute -3 for x into (3).

(3)-----> y  =  6 + 4(-3)

y  =  6 - 12

y  =  -6

Therefore, the solution is

(x, y)  =  (-3, -6)

Problem 2 :

Solve the following system of equations using substitution.

2x + y = 20  and  6x - 5y = 12

Solution :

2x + y  =  20 -----(1)

6x - 5y  =  12 -----(2)

Step 1 :

Solve (1) for y.

2x + y  =  20

Subtract 2x to each side.

y  =  20 - 2x -----(3)

Step 2 :

Substitute (20 - 2x) for y into (2).

(2)-----> 6x - 5(20 - 2x)  =  12

6x - 100 + 10x  =  12

Simplify.

16x - 100  =  12

16x  =  112

Divide each side 16.

x  =  7

Step 3 :

Substitute 7 for x into (3).

(3)-----> y  =  20 - 2(7)

y  =  20 - 14

y  =  6

Therefore, the solution is

(x, y)  =  (7, 6)

Problem 3 :

Solve the following system of equations using substitution.

y = -2 and 4x - 3y = 18

Solution :

y  =  -2 -----(1)

4x - 3y  =  18  -----(2)

From (1), substitute -2 for y into (2).

4x - 3(-2)  =  18

4x + 6  =  18

Subtract by 6 from each side.

4x  =  12

Divide each side by 4.

x  =  3

Therefore, the solution is

(x, y)  =  (3, -2).

Problem 4 :

Solve the following system of equations using substitution.

2x + 3y = 5  and  3x + 4y = 7

Solution :

2x + 3y  =  5 -----(1)

3x + 4y  =  7 -----(2)

Step 1 :

Multiply (1) by 3.

(1) ⋅ 3 -----> 6x + 9y  =  15

Solve for 6x.

6x  =  15 - 9y -----(3)

Step 2 :

Multiply (2) by 2.

(2) ⋅ 2 -----> 6x + 8y  =  14

From (3), substitute (15 - 9y) for 6x.

(15 - 9y) + 8y  =  14

Simplify.

15 - 9y + 8y  =  14

15 - y  =  14

Subtract 15 from each side.

-y  =  -1

Multiply each side by (-1).

y  =  1

Step 3 :

Substitute 1 for y into (3).

(3)-----> 6x  =  15 - 9(1)

6x  =  15 - 9

6x  =  6

Divide each side by 6.

x  =  1

Therefore, the solution is

(x, y)  =  (1, 1) After having gone through the stuff given above, we hope that the students would have understood, how to solve system of linear equations by substitution method.

Apart from the stuff given in this section, if you need any other stuff in math, please use our google custom search here.

You can also visit our following web pages on different stuff in math.

WORD PROBLEMS

Word problems on simple equations

Word problems on linear equations

Algebra word problems

Word problems on trains

Area and perimeter word problems

Word problems on direct variation and inverse variation

Word problems on unit price

Word problems on unit rate

Word problems on comparing rates

Converting customary units word problems

Converting metric units word problems

Word problems on simple interest

Word problems on compound interest

Word problems on types of angles

Complementary and supplementary angles word problems

Double facts word problems

Trigonometry word problems

Percentage word problems

Profit and loss word problems

Markup and markdown word problems

Decimal word problems

Word problems on fractions

Word problems on mixed fractrions

One step equation word problems

Linear inequalities word problems

Ratio and proportion word problems

Time and work word problems

Word problems on sets and venn diagrams

Word problems on ages

Pythagorean theorem word problems

Percent of a number word problems

Word problems on constant speed

Word problems on average speed

Word problems on sum of the angles of a triangle is 180 degree

OTHER TOPICS

Profit and loss shortcuts

Percentage shortcuts

Times table shortcuts

Time, speed and distance shortcuts

Ratio and proportion shortcuts

Domain and range of rational functions

Domain and range of rational functions with holes

Graphing rational functions

Graphing rational functions with holes

Converting repeating decimals in to fractions

Decimal representation of rational numbers

Finding square root using long division

L.C.M method to solve time and work problems

Translating the word problems in to algebraic expressions

Remainder when 2 power 256 is divided by 17

Remainder when 17 power 23 is divided by 16

Sum of all three digit numbers divisible by 6

Sum of all three digit numbers divisible by 7

Sum of all three digit numbers divisible by 8

Sum of all three digit numbers formed using 1, 3, 4

Sum of all three four digit numbers formed with non zero digits

Sum of all three four digit numbers formed using 0, 1, 2, 3

Sum of all three four digit numbers formed using 1, 2, 5, 6 